Screening of Polysaccharide-Lytic Enzymes by Aspergillus Oryzae on Corncob (Zea mays) and Banana Peel (Musa acuminata Colla) - Elya Mufidah; Audrya Nasywa Veliska; Adib Maula Mifzal; Lorine Tantalu (Universitas Tribhuwana Tunggadewi Malang, 2025)
Polysaccharide-lytic enzymes (PLEs)â€”xylanase, pectinase, amylase, Î²-glucosidase and endoglucanaseâ€”play key roles in the food, feed and bioenergy sectors by converting lignocellulosic waste into fermentable sugars. This study evaluated the ability of Aspergillus oryzae to produce these five PLEs on two abundant yet under-utilised agro-industrial residues: corn cobs (Zea mays) and banana peels (Musa acuminata balbisiana Colla). Submerged fermentation was performed using 1 % (w/v) substrate at 30 Â°C and 120 rpm. Enzyme activities were determined colorimetrically, and differences between substrates were analyzed using Mannâ€“Whitney U test whereas the starch- and pectin-rich banana peels favour pectinase, amylase, glucosidase and endoglucanase, Spearmanâ€“Kendall correlation, and linear regression. The highest xylanase titre (12.8 Â± 0.2 IU mLâ»Â¹) was achieved with corn cobsâ€”about 1.5-fold higher than with banana peels (p 0.05). Conversely, banana peels significantly boosted pectinase (2.5 IU mLâ»Â¹), amylase (14.0 IU mLâ»Â¹), Î²-glucosidase (18.1 IU mLâ»Â¹) and endoglucanase (15.2 IU mLâ»Â¹) compared with corn cobs (p 0.05). Strong negative correlations (Ï â‰ˆ âˆ’0.85 to âˆ’0.95) were observed between xylanase and the other enzymes, while the latter showed very strong positive intercorrelations (Ï â‰ˆ 0.81â€“0.98). Linear regression confirmed that substrate type significantly affected enzyme yields (RÂ² 0.90; p 0.001). These findings indicate that corn cobs are the most effective substrate for xylanase production, whereas banana peels better support pectinase, amylase, Î²-glucosidase, and endoglucanase synthesis. The results highlight the importance of selecting appropriate agro-waste substrates to maximise enzyme production and sustainably valorise agricultural residuesÂ